Морфобіологічні особливості та перспективи використання у декоративному садівництві украЇни Argemone mexicana L. (Papaveraceae Juss.) - Horai, H.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The purpose – to study of morphobiological aspects of Argemone mexicana L. (Papaveraceae Juss.) growth, development and seed productivity in a culture in M.M. Gryshko National Botanical Garden of the NAS of Ukraine (NBG). Material and methods. A. mexicana is annual ornamental plant. The research of the ontogenetic development was based on I.P. Ignatieva (1983). Phenological observations were carried out according to R.A. Carpysonova (1972). Seed productivity was determined by the method of I.V. Vaynahiy (1993). Results. The plants of A. mexicana were characterized by rapid development in a culture of NBG. Formation of vegetative sphere of plants continued for 30–33 days. The flowering phase was observed on the 46–48th day after germination, the appearance of the first ripe fruit on the 78th day. The leaf series consisted of six leaves. Changes of leaf morphology were not only in the increasing of size, but in the increasing divisions of leaf and the complications of its form also. From 24 to 45 flowers were forming on one plant. The phase of flowering continued for more than two months. Seeds productivity of the plant was 6650 seeds on average. Duration of generative period was 116–149 days. Conclusions. Annual cycle of development of A. mexicana in conditions of NBG ends with a normal fruiting marked by high level of seed productivity. The plants of A. mexicana are characterized by a short period of vegetative development and a long generative period. The perspectives of use of A. mexicana in gardening are designed according to data obtained.